Retinal Vessel Responses to Flicker Stimulation Are Impaired in Cav2.3-Deficient Mice—An in-vivo Evaluation Using Retinal Vessel Analysis (RVA) - Neumaier, Felix; Kotliar, Konstantin; Haeren, Roel Hubert Louis; Temel, Yasin; Lüke, Jan Niklas; Seyam, Osama; Lindauer, Ute; Clusmann, Hans; Hescheler, Jürgen; Schubert, Gerrit Alexander; Schneider, Toni; Albanna, Walid (Frontiers in Neurology, 2021)
Objective Metabolic demand increases with neuronal activity and adequate energy supply is ensured by neurovascular coupling (NVC). Impairments of NVC have been reported in the context of several diseases and may correlate with disease severity and outcome. Voltage-gated Ca2+-channels (VGCCs) are involved in the regulation of vasomotor tone. In the present study, we compared arterial and venous responses to flicker stimulation in Cav2.3-competent (Cav2.3[+/+]) and -deficient (Cav2.3[-/-]) mice using retinal vessel analysis. Methods The mice were anesthetized and the pupil of one eye was dilated by application of a mydriaticum. An adapted prototype of retinal vessel analyzer was used to perform dynamic retinal vessel analysis. Arterial and venous responses were quantified in terms of the area under the curve (AUCart/AUCven) during flicker application, mean maximum dilation (mMDart/mMDven) and time to maximum dilation (tMDart/tMDven) during the flicker, dilation at flicker cessation (DFCart/DFCven), mean maximum constriction (mMCart/mMCven), time to maximum constriction (tMCart/tMCven) after the flicker and reactive magnitude (RMart/RMven). Results A total of 33 retinal scans were conducted in 22 Cav2.3[+/+] and 11 Cav2.3[-/-] mice. Cav2.3[-/-] mice were characterized by attenuated and partially reversed arterial and venous responses, as reflected in significantly lower AUCart (p=0.031) and AUCven (p=0.047), a trend towards reduced DFCart (p=0.100), DFCven (p=0.100), mMDven (p=0.075) and RMart (p=0.090) and a trend towards increased tMDart (p=0.096). Conclusion To our knowledge, this is the first study using a novel, non-invasive analysis technique to document impairment of retinal vessel responses in VGCC-deficient mice. We propose that Cav2.3 channels could be involved in NVC and may contribute to the impairment of vasomotor responses.